The MUSIC of galaxy clusters – II. X-ray global properties and scaling relations. Issue 1 (31st January 2014) - Biffi, V.; Sembolini, F.; De Petris, M.; Valdarnini, R.; Yepes, G.; Gottlöber, S.
Abstract: We present the X-ray properties and scaling relations of a large sample of clusters extracted from the Marenostrum MUltidark SImulations of galaxy Clusters (MUSIC) data set. We focus on a sub-sample of 179 clusters at redshift z ∼ 0.11, with 3.2 × 10 14   h −1  M⊙ < M vir < 2 × 10 15   h −1  M⊙, complete in mass. We employed the X-ray photon simulator phox to obtain synthetic Chandra observations and derive observable-like global properties of the intracluster medium (ICM), as X-ray temperature ( T X ) and luminosity ( L X ). T X is found to slightly underestimate the true mass-weighted temperature, although tracing fairly well the cluster total mass. We also study the effects of T X on scaling relations with cluster intrinsic properties: total ( M 500 and gas M g, 500 mass; integrated Compton parameter ( Y SZ ) of the Sunyaev-Zel'dovich (SZ) thermal effect; Y X = M g, 500    T X . We confirm that Y X is a very good mass proxy, with a scatter on M 500 - Y X and Y SZ - Y X lower than 5 per cent. The study of scaling relations among X-ray, intrinsic and SZ properties indicates that simulated MUSIC clusters reasonably resemble the self-similar prediction, especially for correlations involving T X . The observational approach also allows for a more direct comparison with real clusters, from which we find deviations mainly due to the physical description of the ICM, affecting T X and, particularly, L X .